Sorption and Ion Exchange Behaviour of Natural Zeolite Packing - Purnomo, Chandra Wahyu; Lenora, Bernice; Budhijanto, Wiratni; Hinode, Hirofumi (UI Scholars Hub, 2017)
It is well known that zeolite is an efficient metal ions adsorbent. The excess charge of the zeolite building blocks i.e. (AlO4)-5 and (SiO4)-4 creating a negative surface charge that attract metal cations. Beside the surface charge, zeolite also has three dimensional pore structure and reasonably large surface area which also can be used as adsorption sites. Ease of cation uptake make it suitable for many process with adsorption and desorption application. This study was conducted to observe the sorption and ion exchange behaviour of zeolite-betonite rings toward iron and cobalt cations. The results shows that the adsorption patterns follow Langmuir isotherm with the highest uptake capacity is 59,9 mg/g for Fe(II) and 57. 8 mg/g for Co(II).